Confirmatory factor analysis of marketing performance dimensions: a lesson from SMEs in Malang, Indonesia - Resanti Lestari; Syahyuti; Berto Mulia Wibawa; Fatmasari Endayani; Dyah Setyawati; Sahat Aditua Fandhitya Silalahi (Cogent Business & Management, 2024)
Literature on marketing has been extensive, with attention given mostly to measuring performance. This article extends the body of knowledge by focusing on the evolution of marketing measurement and the emerging trends. The novelty lies in the involvement of developing-country SMEs, with the goal of developing a model for measuring SMEs' marketing performance. A simple random sampling was used to survey 101 SMEs in Malang, Indonesia. The data was analyzed using SEM PLS. The findings show six dimensions to measure marketing performance in SMEs: product market level, marketing effectiveness, customers, financial performance, marketing efficiency, and adaptability. This study contributes to the existing literature on marketing performance and fills a gap by exploring the financial, market-related, and internal aspects from an SME's perspective. The practical implication is that SMEs need to encourage business activities and adapt the measurement based on these marketing performance dimensions. In addition, the findings can help SMEs with self-learning processes. They can measure marketing performance, identify the weaknesses and strengths of their business, and understand their business positioning. For researchers and policymakers, this study provides insight into the current state of SMEs and their level of maturity.Resanti LestariResearch DescriptionSME growth has numerous challenges despite being a sector that significantly boosts Indonesia's GDP. SMEs struggle with a number of issues, including their inability to carry out comprehensive, logical analyses based on data.This research can assist to giving understanding about how SMEs measure their Marketing Performance. Marketing performance measurement is a form of corporate control in management and the form is an instrument used to assess the overall performance of marketing. This research examines the search for a form of marketing measurement that is suitable for the SME sector. Purpose of this study, is to construct a marketing performance measurement model with dimensions and measurements that are only needed by the SME sector. This research provides implications in the form of a marketing measurement guidance model needed for SMEs.
Keywords: 650; Confirmatory factor analysis; marketing audit; marketing performance; small medium enterprise